Volume viscosity and internal energy relaxation: Error estimates. (October 2018) - Giovangigli, Vincent; Yong, Wen An
Abstract: We investigate the fast relaxation of internal energy in nonequilibrium gas models derived from the kinetic theory of gases. We establish uniform a priori estimates and existence theorems for symmetric hyperbolic–parabolicsystems of partial differential equations with small second order terms and stiff sources. We prove local in time error estimates between the out of equilibrium solution and the one-temperature equilibrium fluid solution for well prepared data and justify the apparition of volume viscosity terms .